2022
DOI: 10.1097/prs.0000000000009912
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high intensity micro-focused ultrasound (HIFU) therapy for non- surgical facial and body contouring: A systematic review of Prospective and Experimental Studies.

Abstract: Background: Liposuction, the most common body sculpting surgical procedure known today is associated with the risk of numerous complications. A safer and more noninvasive approach involves the use of high-intensity focused ultrasonography (HIFU) lasers, which work by selectively damaging fat tissue through apoptosis or necrosis induction of fat cells. The authors' systematic review was designed to identify the effectiveness of HIFU for nonsurgical facial and body contouring. Methods: An exhaustive literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Furthermore, HIFU offers advantages in the formation and reorganization of collagen, and a potential explanation for this effect could be an elevation in TGF-β levels along with the inhibition of MMP3 activity [24]. Furthermore, HIFU is recognized for its capability in non-surgical facial and body contouring, providing a safer and non-invasive alternative to traditional methods, effectively targeting fat tissue for contouring purposes in areas such as the abdomen, face, and neck [28]. Additionally, HIFU is known for its safety, with the most common adverse effect being transient pain during the procedure, while other significant adverse effects are notably rare, thus establishing it as a relatively safe option for skin treatment [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HIFU offers advantages in the formation and reorganization of collagen, and a potential explanation for this effect could be an elevation in TGF-β levels along with the inhibition of MMP3 activity [24]. Furthermore, HIFU is recognized for its capability in non-surgical facial and body contouring, providing a safer and non-invasive alternative to traditional methods, effectively targeting fat tissue for contouring purposes in areas such as the abdomen, face, and neck [28]. Additionally, HIFU is known for its safety, with the most common adverse effect being transient pain during the procedure, while other significant adverse effects are notably rare, thus establishing it as a relatively safe option for skin treatment [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although the lipolytic effects of HIFU have been well reported, there is a lack of research on overall metabolic changes [19]. A meta-analysis of metabolic changes with non-surgical fat removal including HIFU conducted by Badran et al [20] found that 2 units of body mass index, 1 kg of body weight, 5 cm of waist circumference, and 1.5 cm of abdominal fat thickness were maintained up to 60 days after treatment.…”
Section: Discussionmentioning
confidence: 99%